Restoration of degraded lands through bioenergy plantations. Issue 2 (27th January 2020) - Singh, Saurabh; Jaiswal, Durgesh Kumar; Krishna, Ram; Mukherjee, Arpan; Verma, Jay Prakash
Abstract : Land degradation has become a worldwide problem. Increasing population, the conversion of forest land into cropland, and its gradual degradation due to unsustainable agricultural practices have led to this prevailing scenario. Unsustainable agriculture practices like use of chemical fertilizers for increasing crop productivity (recorded 281.75 lakh tonnes in the year 2010–2011) also leads to degradation of land. A total of 4.1 million hectares of culturable wasteland was recorded in the same year. Also, crude oil consumption is increasing at a rate of 1.7% which prompts for massive input of crude oil. Thus, biofuel plantations have recently attracted a lot of attention because of several advantages that they present. The genetically engineered bioenergy crops can help in land restoration by increasing the soil fertility, growing in stress conditions, and they also lead to the production of fuels through their various parts. The use of genetically engineered bioenergy crops will not only help in the prevention of degraded land but also yield biofuel as a product and enhance soil fertility and health for further sustainable agricultural practices.